Fish ladder of Lajeado Dam: migrations on one-way routes? - Agostinho,Angelo Antônio (2007)
Fish ladders are generally conceived to reestablish connectivity among critical habitats for migratory species, thus mitigating the impacts of the blockage of migration routes by dams. If this management tool is to be meaningful for conserving fish species, it must provide a fully permeable connection and assure both upward and downward movements. However, because reservoirs have very different hydrodynamics than the original river, it is expected that, at least in the inner area, they may constitute an additional barrier to this movement, especially for descending fish. Thus, the present study sought to determine if migratory fish and their offspring disperse downstream from the dam after ascending a ladder and spawning in the upper reaches of a basin. To achieve this purpose, we evaluated the limitation imposed by lentic areas to the descent of eggs, larvae and adults of migratory species; we also determined the abundance and composition of larvae present in the plankton near the dam, and compared the intensity of the upward and downward movements of adult fish. Samples of ichthyoplankton were taken upriver, inside the reservoir, in the river downstream from the dam, and in the forebay of the Lajeado Dam on the Tocantins River (Luis Eduardo Magalhães Hydroelectric Plant), from October, 1999 through September, 2004. The densities of fish ascending and descending the ladder were determined experimentally on eight occasions, from June, 2004 to March, 2005. Due to difficulties in identifying the true fish origin (up or down) in the environments connected by the fish passage system, the evaluation of the distribution of migratory fish in reservoirs was based on the landings of the commercial fishery conducted along the Itaipu Reservoir during the four years preceding (2001 through 2003) the construction of the lateral channel (fish-passage mechanism). Fish eggs and larvae drifting down the Tocantins River did not appear in samples taken in the lower half of the reservoir; those found in water flowing through the spillways, turbines or fish ladder of Lajeado Dam belonged essentially to non-migratory clupeids that spawn in the inner part of the reservoir. In addition, results showed that in a reservoir with no fish-passage mechanism, migrants select habitats that still maintain riverine characteristics, in the upper parts of the impounded area. The downward movements are negligible compared to those upward, in the experiments conducted in the fish ladder. It is concluded, therefore, that the Lajeado fish ladder, and possibly those at other dams, is essentially a one-way route that promotes upstream movements of migrants, without the necessary return of adults or their offspring. Thus, the low permeability of the connections provided by these management tools can drastically increase the level of environmental impact that they were actually intended to reduce.